Thyroid-Related Hormone Levels in Clinical Patients With Moderately Severe-to-Profound Sudden Sensorineural Hearing Loss: A Prospective Study - Zheng, Zhong; Shen, Ying; Xia, Liang; Xiao, Lili; Sun, Yuanyuan; Wang, Hui; Chen, Zhengnong; Wu, Yaqin; Shi, Haibo; He, Jingchun; Feng, Yanmei; Yin, Shankai (Frontiers in Neurology, 2021)
Objectives: Sudden sensorineural hearing loss (SSNHL) is a common otological emergency, causing a measure of hearing loss and affecting the quality of life. This study aims to investigate the association of thyroid-related hormone levels with moderately severe-to-profound SSNHL. Methods: The study included 70 patients with moderately severe-to-profound SSNHL and 100 age and sex-matched healthy controls. Peripheral venous blood samples were taken from the participants, and their thyroid-related hormone levels were measured at admission and one week after treatment. Results: In moderately severe-to-profound SSNHL patients, the concentrations of total triiodothyronine (TT3), total thyroxine (TT4), free triiodothyronine (FT3), and thyroid-stimulating hormone (TSH) (all P < 0.05) were significantly lower than in the control group. The TT3, TT4, FT3, and TSH levels were significantly higher in the effective group than in the ineffective group (all P < 0.05). Linear correlation analysis revealed that TSH level (R=0.707, P < 0.05) elevation after treatment successfully predicted a favourable outcome of hearing recovery. Logistic regression analyses suggested low FT3 and TSH levels to be independent occurrence predictors, while the increase of TSH level may be an independent favourable outcome predictor. Conclusions: The results suggest that low FT3 and TSH levels are risk factors for moderately severe-to profound SSNHL. By discovering the positive association between TSH elevation and hearing recovery, along with the potential novel predictors of FT3 and TSH, our study may contribute valuable insights to the research and treatment of moderately severe-to-profound SSNHL.